Functional Screening of Parkinson’s Disease Susceptibility Genes to Identify Novel Modulators of α-Synuclein Neurotoxicity in Caenorhabditis elegans - Vozdek, Roman; Pramstaller, Peter P.; Hicks, Andrew A. (Frontiers in Aging Neuroscience, 2022)
Idiopathic Parkinson’s disease (PD) is characterized by progressive loss of dopaminergic (DA) neurons during aging. The pathological hallmark of PD is the Lewy body detected in postmortem brain tissue, which is mainly composed of aggregated α-Synuclein (αSyn). However, it is estimated that 90% of PD cases have unknown pathogenetic triggers. Here, we generated a new transgenic Caenorhabditis elegans PD model eraIs1 expressing green fluorescent protein- (GFP-) based reporter of human αSyn in DA neurons, and exhibited a nice readout of the developed αSyn inclusions in DA neurons, leading to their degeneration during aging. Using these animals in a preliminary reverse genetic screening of >100-PD genome-wide association study- (GWAS-) based susceptibility genes, we identified 28 orthologs of C. elegans and their inactivation altered the phenotype of eraIs1; 10 knockdowns exhibited reduced penetrance of αSyn:Venus inclusions formed in the axons of cephalic (CEP) DA neurons, 18 knockdowns exhibited increased penetrance of disrupted CEP dendrite integrity among which nine knockdowns also exhibited disrupted neuronal morphology independent of the expressed αSyn reporter. Loss-of-function alleles of the five identified genes, such as sac-2, rig-6 or lfe-2, unc-43, and nsf-1, modulated the corresponding eraIs1 phenotype, respectively, and supported the RNA interference (RNAi) data. The Western blot analysis showed that the levels of insoluble αSyn:Venus were not correlated with the observed phenotypes in these mutants. However, RNAi of 12 identified modulators reduced the formation of pro-aggregating polyglutamine Q40:YFP foci in muscle cells, suggesting the possible role of these genes in cellular proteotoxicity. Therefore, modulators identified by their associated biological pathways, such as calcium signaling or vesicular trafficking, represent new potential therapeutic targets for neurodegenerative proteopathies and other diseases associated with aging.